Dynamics of Non-Isothermal Pressure-Driven Flow of Generalized Viscoelastic-Fluid-Based Nanofluids in a Channel - Khan, Idrees; Chinyoka, Tiri; Gill, Andrew (Mathematical problems in engineering, 2022)
The investigation considers numerical analysis and computational solution of unsteady, pressure-driven channel flow of a generalized viscoelastic-fluid-based nanofluid (GVFBN) subject to exothermic reactions. Temperature-dependent fluid thermal conductivity is considered, and the flow is subject to convective cooling at the walls. The non-isothermal generalized Giesekus constitutive model is employed for the GVFBN. A Carreau model is used to describe the shear-rate dependence of fluid viscosity, and exothermic reactions are assumed to follow Arrhenius kinetics. An efficient semi-implicit numerical technique based on the finite-difference method is applied to obtain computational solutions to the model equations. The computational methodologies are built into the MATLAB software. The effects of various fluid and flow parameters, specifically the nanoparticle volume fraction, are explored. The results demonstrate that those parameters which only directly couple to the energy equation (but are otherwise indirectly coupled to momentum and stress-constitutive equations, say via the temperature-dependent viscosities and relaxation times) would only show prominent effects on fluid temperature but not on the fluid velocity or the polymer stresses. The results also demonstrate, as in the literature on exothermic flows, that the values of exothermic-reaction parameter must be carefully controlled as large values would lead to thermal runway phenomena. The illustrated results are consistent with the existing literature and additionally add novel new contributions to non-isothermal and pressure-driven channel flow of GVFBN under convective cooling conditions.